Illusory competitiveness : the apparel assembly model of the Caribbean Basin - Mortimore, Michael (CEPAL SantiagoCL, 2003)
Notes that exports of apparel represent the principal link of the Caribbean Basin to the international economy. Suggests that this model produces an illusory competitiveness based on artificial advantages, not an authentic competitiveness that improves the productive base of the economy by way of the transfer of modern technologies, the creation of deeper linkages, more specialized training and enterprise development.